Medical students prefer print textbooks for studying but value the e-books’ search function and availability (Journal of EAHIL, 2020)
Since a few years our library has mostly acquired journals only in electronic format, whereas medical textbooks are often provided in print and as e-books. In order to meet the students’ current needs and to reasonably allocate financial means and efforts, we performed a survey about format preferences amongst medical students at the University of Zurich, Switzerland. 94 medical students returned our questionnaire in December 2018 (4.6% response rate). The survey showed that print books were used more often, especially for longer reading, but e-books were also commonly used. Perceived advantages of print books were the possibilities to mark text passages and better eye comfort. E-books were valued for their search function and availability.